Regional Office for Aid to the Victims of War in Prague (1919–1938) - Hubený, David; Kruglova, Nadezda (Faces of War, 2024)
The killings and mutilations brought about by World War I left a significant mark on society: missing husbands and fathers, surviving war veterans, widows and orphans. The newly formed Czechoslovakia had to deal with this tragic legacy and care for the 600,000 men, women, and children affected by the war. To do this, it was necessary to strengthen the relevant public administration apparatus, as the existing social security was not prepared for such a burden. The new state could not fail where the Habsburg monarchy had already failed, ceasing to perform its basic social and economic functions for its population. The Czechoslovak Republic, consisting of several higher-level administrative-territorial units called ‘lands’ (země), began to create regional offices and authorities to provide care for disabled soldiers or men who had fallen ill as a result of military service, widows of deceased soldiers, widows of disabled veterans of the war and post-war years, as well as parents of deceased or disabled victims of the war and from the post-war years. This paper will describe the legislative framework of the authorities using the example of the Regional Office for Aid to the Victims of War in Prague, its functioning and organisation of personnel, as well as the types of cases handled by the authorities and their reception by society.